Status of anemia among the tribal children in West Bengal - Ray, Rudra; Bhattacharyya, Maitreyee (International Journal Of Community Medicine And Public Health, 2021)
Background: Anemia is a major public health problem worldwide. School children are more vulnerable to this disease due to their rapid growth need of high iron. Therefore, it is a critical health concern because it affects growth and physical performance. This study was undertaken to investigate the prevalence of anemia among different areas and sub-caste of tribal school children in West Bengal. Methods: Complete hemogram was performed on Sysmex (KX-21) automated cell counter. Haemoglobin analysis was done by high performance liquid chromatography (HPLC, from Bio Rad Variant II). Ferritin estimation was done by ELISA based method. A software (Thaltribe) was prepared to record and maintain the data of the screened population. Results: Total number of school students from all the districts of West Bengal included in this study was 45887. Among the total population 49.88% were found to carry low Hb and 28.45% had low ferritin. Among the population who had normal ferritin (N=32832), there were 46.59% (N=15298) carrying low Hb. Among total 15298 cases who had low Hb with normal ferritin level, 10741 (70.21%) remained undiagnosed who were not detected to be thalassaemia carrier or thalassaemia disease (HPLC normal) and also did not carry alpha globin gene mutation. Conclusions: On the contrary to the common belief that iron is the main source of anemia, it was observed in this study that around 25% of anemic children did not have iron deficiency. This group requires further evaluation to investigate the reason of anemia.